Conocimiento y criterio de enfermería para evitar flebitis en neonatos con catéter venoso periférico - Velázquez Mendoza, Sabina (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
The daily and daily of attention and taken care of process of the newborn ones offers the opportunity us to know, to observe and to implement procedures that contribute to the well-being of the newborn Objective: To analyze the knowledge and the criterion of infirmary to avoid that the phlebitis in the newborn one with peripheral venous catheter appears. Methodology: The design of the investigation was cross-sectional, descriptive and observacional to 17 nurses and 43 newborn ones entered to the service of pediatric infectología. An instrument was applied where 3 dimensions were evaluated: knowledge, criterion and technique. Another instrument was the list of I collate to measure the phlebitis that contains the indicators of quality of the Official Norm in the monitoring and control of venoclisis installed of the SSA (2001). Results: This way evidence that the phlebitis is one of the main problems of the use of short intravenous catheters. In the group of age of 20 to 25 years it contributed statistical significance, in the technique (F=4.663, gl=3, sig: =.020) is the one who better takes it I end an average of execution of 2.25, With regard to knowledge and criterion are statistically no significant numbers. Discussion: The results found in this study demonstrate that the phlebitis risk is increased when increasing the dwell time of the devices you will intratilt peripheral because they present/display phlebitis in the first 24 to 48hrs. Of installed a peripheral venous catheter. Conclusions: We did not reject the Ho “the presence of the phlebitis in the newborn one with hospitalized peripheral venous catheter appears not only because the cares of infirmary are inadequate to avoid this complication, but that influence other external factors as they are the lack of material adapted for the canalization.

El proceso diario y cotidiano de atención y cuidado de los neonatos nos brinda la oportunidad de conocer, observar e implementar procedimientos que contribuyen al bienestar del neonato Objetivo: Analizar el conocimiento y el criterio de enfermería para evitar que se presente la flebitis en el neonato con catéter venoso periférico. Metodología: El diseño de la investigación fue transversal, descriptivo y observacional a 17 enfermeras y 43 neonatos ingresados al servicio de infectología pediátrica. Se aplicó un instrumento donde se evaluaron 3 dimensiones: conocimiento, criterio y técnica. Otro instrumento fue la guía de observación para medir la flebitis que contiene los indicadores de calidad de la Norma Oficial en la vigilancia y control de venoclisis instaladas de la SSA (2001). Resultados: De esta manera se evidencia que la flebitis es uno de los principales problemas del uso de catéteres intravenosos cortos. En el grupo de edad de 20 a 25 años aportó significancia estadística, en la técnica (F=4.663, gl=3, sig:=.020) es quien mejor lo lleva acabo con un promedio de ejecución de 2.25, En lo que respecta a conocimiento y criterio no hay cifras estadísticamente significativas. Discusión: Los resultados encontrados en este estudio demuestran que el riesgo de flebitis se incrementa al aumentar el tiempo de permanencia de los dispositivos intravasculares periféricos porque presentan flebitis en las primeras 24 a 48hrs. de instalado un catéter venoso periférico. Conclusiones: NO rechazamos la Ho “La presencia de la flebitis en el neonato con catéter venoso periférico hospitalizado se presenta no sólo porque los cuidados de enfermería son inadecuados para evitar esta complicación, sino que influyen otros factores externos como son la falta de material adecuado para la canalización.
Facultad de Enfermería. Maestría en Enfermería
Keywords: info:eu-repo/classification/cti/3; FE-M-2008-0002; Neonatos; Catéter venoso; Flebitis; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5610